Standing Aufem hose
Standing Aufem hose
If the question is really: What is the root of f (x) = 2, then the answer is: F (x) = 2x + c for any food Ante c.
See the math formula book under integration rules. Here basic integrals.
S x ^ k * dx = x ^ (k + 1) / (k + 1) for k not equal to - 1 and for k <0 x equal to 0
y '= 2 = 2 * x ^ 0 integrated yields y = F (x) = 2 * x + c The integration constant c always occurs because the differentiating removes a constant !!
F (x) = 2x + C
F (x) = 2x + C
because if you ableitest this function is the result of f (x) = 2
Hi, I custom umbedingt the walkthrough for the antiderivative of v / -gk * v ^ 2 dv the solution I've attached a picture. I'm all about not die on the 2k. Thanks in advance! --answer-- Leite solving some games from, then you point where it comes fr
Hello, I'm sitting on a task and do not get ahead somehow: Determine the parameter a such that F (x) = (a-2x) e ^ x / 2 is a primitive function of f (f (x) = (4-x) e ^ x / 2 Is. Can anyone explain how I can figure that? Thank you! --answer-- Why so c
Hello, the primitive function of (x / (x + 1)) is a "well-known table-valued" or you would for making a calculation method? --answer-- Hello ! a "known table value" I have the book "Power - formulas of mathematics" at home. T
Can anyone aufleiten -2x me or which form the primitive? Thank you. --answer-- Hello! You must you simply think of what function "-2x" could be the derivative! This is actually quite simple ... Since the question is however determined deleted an
Hey folks hab grad problems in a task get the antiderivative not go ... f (x) = x-2 can anyone help me on the jumps: / can not otherwise expect further --answer-- As in deriving, one function takes also in integrating piecemeal. So if you just stand
What is the function of stem: (2 / s ^ 2) * x? Best regards --answer-- The master function is: F (x) = ((2 / d ^ 2) * x ^ 1 + 1) / (1 + 1) + C = ((2 / e ^ 2) * x ^ 2) / 2 + c = 1x ^ 2 / e ^ 2 + c f (x) = (2 / e) x, F (x) = (1 / e²) x² = x² / e = (x /
Hello first, learning grade math and need urgent help. So why is f (x) = ln (3) the primitive function F (x) = ln (3) x? Because actually is yes at f (x) = ln (x) the primitive function F (x) = x ln (x) -x. So why is the primitive function of f (x) =
Hello in school we have just the theme primitives. I understand that not really. Could you explain that to me again exactly at the example: 1 / root (x) The teacher said we should first convert the function into a power. And then form the primitive f
Happy New Year ! How to plot the graph of the primitive from the graph of its derivative? --answer-- this you need to know: where dissipation of the x-axis, as falls f; (On the x-axis as rising f) where derivative zero, because f has extreme point wh